The Discourse Marker מ ה ז ה (ma ze) to express Rebuking in Rabbinic Hebrew - Shemesh-Raiskin, Rivka (Journal of Semitic studies, 2022)
The phrase מ ה ז ה (ma ze) is used in Rabbinic Hebrew to express a speech act of rebuking, for example: ? מהזה, עקיבא (‘What is this, ʿAqiba?’). A review of its occurrences reveals its various characteristics: a) it serves as a rhetorical question to express a rebuking; b) it appears in the spoken language; c) it is used especially by one sage when rebuking another sage; and d), syntactically, it appears at the beginning of the sentence and is followed by an address. It seems that its usage in Rabbinic Hebrew is not a continuation of the usage found in Biblical Hebrew, and that it has not continued into Modern Hebrew. This usage as described and exemplified in this article has apparently not been documented in dictionaries of Rabbinic Hebrew nor in the research literature. I suggest viewing מ ה ז ה Hebrew as a rebuking interactional discourse marker.